THE EFFECTIVENESS OF INTERACTIVE METHODS IN TEACHING THE RUSSIAN LANGUAGE - Рulatova Laziza Saidmurodovna (Sciental Journals Publishing, 2026)
This article examines the effectiveness of interactive methods in teaching the Russian language. It analyzes the shift from traditional passive instructional models to learner-centered approaches in which students become active participants in the educational process. The study identifies key challenges in contemporary Russian language instruction and explores modern solutions grounded in interactive pedagogy. The principal advantages of the interactive approach are highlighted, including individualized learning, the development of critical thinking, and the transformation of the teacher’s role into that of a facilitator. Particular attention is given to the practical implementation of methods that foster communicative competence and students’ confidence in collaborative work.
Keywords: Interactive methods, teaching, Russian language, foreign language, communicative skills, project-based learning, role-playing games, digital technologies.